The Design of a Remediation Device for Heavy Metal Contaminated Soil Under Digital Economy - Li, Yuanyuan; Liu, Jiang; Jia, Shibo (Frontiers in Energy Research, 2022)
Since entering the new era, the economy has grown rapidly and the economic strength has improved significantly, but it is accompanied by resource and environmental problems caused by the high pollution and high energy consumption growth model. Realizing the transformation of economic development from "incremental" to "increasing quality" and promoting economic green transformation has become one of the main development goals of China in the next stage. With the rapid development of China's social economy, the changes of industrialization, urbanization and agricultural intensification are getting faster and faster. The discharge of industrial "three wastes" and urban domestic wastewater has gradually increased, and a large amount of chemical fertilizers and pesticides have been applied to rural arable land. It accelerates soil heavy metal pollution. Electrodynamic remediation technology, as an emerging soil in situ remediation technology, has attracted wide attention due to its advantages of wide range of pollutant removal, low cost and good effect. In this paper, a remediation device for heavy metal-contaminated soil is designed based on electrodynamic remediation technology. That is, on the basis of the digital economy, an electrolyte circulation mechanism with high adsorption of heavy metal ions is introduced. In this paper, the feasibility of electrokinetic remediation of the contaminated soil was investigated, and the effects of electrolyte type, voltage, and remediation time on the removal of heavy metals were studied. The following results were obtained through a series of experimental studies: the pH values of region A in E1, E2, and E3 were 3.24, 3.18, and 3.09, respectively. The current peak values of E1, E2 and E4 are 0.44mA, 0.68mA and 0.75mA respectively. E4 had the best adsorption effect on heavy metal cadmium ions, with an average adsorption rate of 7.3%. The results show that the electrodynamic remediation device can effectively remove heavy metals in soil. It can also recycle the electrolyte solution, which is an environmentally friendly repair device.